Solución de problemas ambientales mediante la Modelación Hidrogeoquímica. - Fagundo Castillo, J. R.; González, P.; Alvarez Varela, E.; Tillán Ochoa, G.; Vinardell Grandal, I.; Fagudo Sierra, J.; Suárez Muñoz, M.; Melián Rodríguez, Cl. (Revista CENIC Ciencias Quimicas)
Several informatic systems (HIDROGEOQUIM, SAMA, GEOQUIM, BATOMET, SACAN, SIMUCIN, MODELAGUA), which has been designed and implemented from 1980 to the present year by the collective of this paper are discussed and with application examples about underground water characterization and quality control. These computer programs are based on thermodynamic and kinetics principles as well as statistics, pattern recognition, mass balance and mixing water models. The last programs were developed in DELPHI language version 3 for WINDOWS.